METODE NABI DAN SAHABAT DALAM MENYAMPAIKAN DAN MEMELIHARA HADIS - Syafiuddin; Moh. Holil (Yayasan Baitul Hikmah al-Zain, 2025)
Hadith is everything that is attributed to the Prophet, so that everything that comes from him can be used as evidence for the Islamic religion. The journey of the Prophet's hadith is different from the Koran which was revealed mutawatirly, while the hadith went through various obstacles in its preservation and even used various methods of transmission. Thus, what was the method of the Prophet and his companions in conveying and maintaining hadith? The method used in this research is qualitative, namely research that focuses on collecting related data and then carrying out descriptive analysis. Also, this research is library research, namely collecting several related references. The Prophet's way of conveying and maintaining hadith included gathering in a knowledge gathering, speaking specifically to his wife if it was related to a sensitive matter, but also to certain friends. Likewise, the companions conveyed what the Prophet conveyed, namely in a knowledge gathering or certain companions who then spread it to other companions who did not yet know it. Meanwhile, regarding the understanding of this hadith which seems to be traditional, the ulama expressed several opinions, such as stating that there is a hadith that is ¬nasīkh mansūkh, there are also those who stated that the hadith was prohibited from being written because of the illat which at that time was feared to be mixed with the Koran.